GEOLOGICAL AND GEOTECHNICAL BEHAVIOUR OF EVINOS DAM FOLLOWING THE IMPOUNDMENT - Angelopoulos, A.; Soulis, V.J.; Malandraki, V. (Bulletin of the Geological Society of Greece, 2010)
The Evinos dam built between 1993 and 1997. The period of construction followed a period of rest until 2001. The impoundment of the Evinos Dam and the subsequent 3rd operational period took place between 2001 and 2005. The 4th period of operation commenced in February 2005 and concerns the period of regular operation of Dam Evinos after completion. During this period, sufficient data have been gathered for the evaluation of the geotechnical behaviour of both Evinos Dam itself and the stabilization works on the two landslides that occurred (Landslide of the left abutment ’93, Landslide of Ag.Demetrios-Arahova country road). Specialized personnel of the Department of the Evinos Dam of the Athens Water Supply and Sewage Company S.A are responsible for the in-situ collection of instrumental readings. On the other hand specialized personnel of the Division of Raw Water Intake of Athens Water Supply and Sewage Company S.A are assigned to evaluate the dam’s behaviour. The infiltration of water within the Dam’s core is continuously monitored together with the horizontal movement and settlement upstream and downstream the dam’s body through a considerable number of vibrating wire piezometers, earth pressure cells, extensiometers, inclinometers and surface monumental stations. The behaviour of the stabilization interventions in the landslide area’s are evaluated through measurement of topographic monuments ,open piezometers and drainage measurements. The evaluation of the instrumental measurerements confirms the expected behavior of the dam and the satisfactory performance of the stabilization interventions in the landslide area’s